2019
DOI: 10.2135/cropsci2019.01.0005
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Nicotiana tabacum to Phytophthora parasitica var. nicotianae Race 0 Is Enhanced by the Addition of N. plumbaginifolia Chromosome 9 with a Slight Effect on Host Genomic Expression

Abstract: Black shank is a devastating disease in tobacco production worldwide, and resistance to this disease in Nicotiana plumbaginifolia Viv. tobacco is controlled by the Php gene. The position of the Php gene on chromosomes of N. plumbaginifolia remains unclear. The tobacco line TP‐1, which was derived from N. tabacum L. cv. Yunyan87 and N. plumbaginifolia, was used in the present study to help locate the Php gene on the N. plumbaginifolia chromosomes and understand the effects of the N. plumbaginifolia chromosome a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In previous studies, we analyzed the differentially expressed genes of the highly resistant tobacco species N. plumbaginifolia and of the moderately resistant cultivar ‘Yunyan 87’ identified by transcriptome sequencing [ 9 ]. A Unigene, c62451.graph_c0, was specifically expressed in N. plumbaginifolia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we analyzed the differentially expressed genes of the highly resistant tobacco species N. plumbaginifolia and of the moderately resistant cultivar ‘Yunyan 87’ identified by transcriptome sequencing [ 9 ]. A Unigene, c62451.graph_c0, was specifically expressed in N. plumbaginifolia.…”
Section: Resultsmentioning
confidence: 99%
“…Their resistance has been successfully transferred to cultivated tobacco by distant hybridization [ 6 ]. A study by Goins and Apple [ 7 ] showed that the resistance of N. longiflora and N. plumbaginifolia is regulated by the major genes Phl and Php , respectively, and the black shank resistance was introgressed into cultivated tobacco as early as 1960 [ 8 , 9 ]. In recent years, researchers have identified the glutathione S-transferase gene in N. tabacum as a negative regulator, and silencing of this gene has been found to promote resistance to black shank in tobacco [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the disease resistance protein RPV1 is known to confer resistance to oomycete and fungal pathogens in cultivated grapevines ( Vitis vinifera) ( Gessler et al., 2011 ). LRR receptor-like serine/threonine-protein kinase GSO1 was reported to be related to the resistance of Nicotiana tabacum to the oomycete Phytophthora parasitica ( Dang et al., 2019 ). TMV resistance protein N-like was reported to be involved in the resistance in potato to the fungus Synchytrium endobioticum ( Hehl et al., 1999 ), and in peanut to two serious fungal foliar diseases ( Dang et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the disease resistance protein RPV1 is known to confer resistance to oomycete and fungal pathogens in cultivated grapevines ( Vitis vinifera) 69 . LRR receptor-like serine/threonine-protein kinase GSO1 was reported to be related to the resistance of Nicotiana tabacum to the oomycete Phytophthora parasitica 70 . TMV resistance protein N-like was reported to be involved in the resistance in potato to the fungus Synchytrium endobioticum 71 , and in peanut to two serious fungal foliar diseases 72 .…”
Section: Discussionmentioning
confidence: 99%